Preparation of SnS2/enteromorpha prolifera derived carbon composite and its performance of sodium-ion batteries. (May 2021) - He, Xiaotong; Liu, Junbin; Kang, Biyu; Li, Xinye; Zeng, Lingxing; Liu, Yanru; Qiu, Jianbin; Qian, Qingrong; Wei, Mingdeng; Chen, Qinghua
Abstract: SnS2 has aroused great interests for application of sodium-ion batteries, because of its graphene-like structure and high theoretical capacity. Herein, we present an effective nanocasting strategy to fabricate the SnS2 / enteromorpha prolifera derived carbon (SnS2 /EPC) composite, whose microstructure anchors the SnS2 nanosheets on enteromorpha prolifera (EP) derived carbon. It can effectively solve the problems of poor conductivity and volume expansion of SnS2 electrode during charging and discharging process. The optimized SnS2 /EPC could deliver high reversible capacity of 443 mA h g −1 at 0.1 A g −1, and maintain reversible capacity of 340 mA h g −1 at high rate of 2 A g −1 after 450 cycles, indicating that SnS2 /EPC is a promising anode material for sodium storage. Graphical abstract: The SnS2 /enteromorpha prolifera derived carbon (SnS2 /EPC) composite is fabricated. When acted as an anode of SIBs, it delivers a high specific capacity of 443 mA h g −1 after 50 cycles at a current density of 0.1 A g −1 and superior rate performance (340 mA h g −1 at 2.0 A g −1 after 450 cycles). Image 1 Highlights: The SnS2 /EPC composite was obtained via a facile nanocasting strategy. The SnS2 nanosheets uniformly anchored on EPC. Enteromorpha prolifera was used as biocarbon precursor. The composite shows stable high rate capacity of 340 mA h g −1 (2 A g −1, 450 cycles).